UPAYA PENGENDALIAN INTENSITAS TANTRUM ANAK USIA DINI YANG DIAKIBATKAN SCREEN TIME - Mauliya, Amel; Sopiah, Cucu; Hizriyani, Rina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Uncontrolled gadget use can negatively affect children’s social emotional development, particulary their ability to regulate emotional. This study aimed to identify and describe efforts to control the intensity of tantrums caused by screen time among early childhood children. This study employed a qualitative approach with a descriptive design, the research subjects consisted of group B teachers, parents, and children aged 5-6 years at TK Bina Mentari, data were collected through observation, interviews, and documentation, the collected data were analyzed using data reduction, data presentation, and conclusion drawing. The result showed that tantrum behavior appeared in the form of excessive crying, screaming, refusing to participate in actities, and aggressive outbursts when gadget use was restricted, the control efforts implemented included limiting screen time duration, conducting parenting programs for parents, providing alternative play activities, and creating educational banner about screen time limitations, good collaboration between schools and families wa proven to gradually reduce the intensity of children’s tantrums and improve their emotional regulation abilities. Based on the finding, it can be concluded the consisten screen time management supported by appropriate parenting practices can help reduce tantrum behavior in early childhood, therefore collaboration between teachers and parents is essential to support children’s optimal sosial emotional development in the digital era.